2019
DOI: 10.7150/jca.28137
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association between Interleukin-4 Receptor Polymorphisms and Cancer Susceptibility: A Meta-Analysis Based on 53 Case-Control Studies

Abstract: Polymorphisms in interleukin-4 receptor (IL-4R) gene have been reported susceptible to a variety of cancer types, nevertheless, data from these publications remained inconsistent and controversial. We further performed a comprehensive meta-analysis to present a precise estimation of its relationship. Extensive retrieve was performed in PubMed, Google Scholar and Web of Science up to May 25, 2018. Odds ratios (ORs) and 95% confidence intervals (CIs) were conducted to evaluate the overall strength of the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…IL-4 is an anti-inflammatory Th2 cytokine that can bind IL-4R to regulate IgE production, immune response, and embryonic implantation [ 13 , 29 , 42 ]. Several studies have reported that polymorphisms of IL-4 and/or IL-4R genes are associated with allergic diseases [ 23 , 24 ], diabetes [ 43 ], cancers [ 36 ], and pregnancy disorders [ 25 , 26 , 27 ]. In the present study, we have verified and elucidated polymorphisms of the porcine IL-4 and IL-4R genes with respect to reproductive performance traits in commercial pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-4 is an anti-inflammatory Th2 cytokine that can bind IL-4R to regulate IgE production, immune response, and embryonic implantation [ 13 , 29 , 42 ]. Several studies have reported that polymorphisms of IL-4 and/or IL-4R genes are associated with allergic diseases [ 23 , 24 ], diabetes [ 43 ], cancers [ 36 ], and pregnancy disorders [ 25 , 26 , 27 ]. In the present study, we have verified and elucidated polymorphisms of the porcine IL-4 and IL-4R genes with respect to reproductive performance traits in commercial pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphisms of the porcine IL-4R gene have been characterized and reported in the Ensembl database (https://asia.ensembl.org/Sus_scrofa/Info/Index, accessed on 2 September 2020). Moreover, the polymorphisms of IL4R gene are associated with the pregnancy disorders and various cancer types in humans [27,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…This increased transcriptional activity is critical for increasing the expression of CD14 gene . Mounting evidence indicates the involvement of gene SNPs in cancer risk …”
Section: Discussionmentioning
confidence: 99%
“…According to the updated global estimation in 2018, approximately 42 million people across the world suffered from any type of cancer. 1 Although great efforts have been made to clarify the mechanisms of carcinogenesis, much remains unknown. Many risk factors that promote carcinogenesis have been identified, such as family history of cancer, dietary habits, alcohol use, obesity, smoking, and occupational exposures.…”
Section: Introductionmentioning
confidence: 99%